2012
DOI: 10.1049/iet-smt.2011.0123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two approaches to compute magnetic field in problems with random domains

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractMethods are now available to solve numerically electromagnetic problems with uncertain input data (behaviour law or geometry). The stochastic approach consists in modelling uncertain data using random variables. Discontinuities on the magnetic field distribution in the stochastic dimension can arise in a problem with uncertainties on the geometry.The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We assume that the domain D is deterministic and is composed by several subdomains, and in each subdomain D i , the random curve B = g i ( H ,θ) is independent of the position x . Random geometries can also be considered , but they are out of the scope of this paper. If the behavior law is assumed linear and random, the curve B = g i ( H ,θ) is linear with a random slope, which is the random permeability μ i (θ).…”
Section: Stochastic Magnetostatic Problem With Uncertainties On the Bmentioning
confidence: 99%
“…We assume that the domain D is deterministic and is composed by several subdomains, and in each subdomain D i , the random curve B = g i ( H ,θ) is independent of the position x . Random geometries can also be considered , but they are out of the scope of this paper. If the behavior law is assumed linear and random, the curve B = g i ( H ,θ) is linear with a random slope, which is the random permeability μ i (θ).…”
Section: Stochastic Magnetostatic Problem With Uncertainties On the Bmentioning
confidence: 99%
“…We have generated two samples of parameter sets of length L equal to 78 and 364 leading to two samples of matrices S To evaluate the quality of the approximation, we have applied the strategy proposed in VII.B by calculating α n DEI (p n ) (see (27)) for each p belonging to P n (see VII.A). We remind that e(p) has been already calculated during the construction of the POD approximation and e r DEI (p) is calculated using the reduced model combining the (D)EI method and the POD method (see (24)) which is very fast. In Fig.8, we give values obtained for 70 snapshots for the four meshes when L=78.…”
Section: Accuracy Of the (D)ei Methodsmentioning
confidence: 99%
“…This technique has been proposed for the stochastic finite element method in [22,23]. Another possibility consists in applying the transformation method proposed in [24,25] which will be used in the following. It can be shown that the parametrization on the geometry can be transferred on a parametrization on the material characteristics [26].…”
Section: A Parametric Finite Element Modelmentioning
confidence: 99%
“…The most natural way to account for randomness on the geometry consist in remeshing according to the deformation but the remeshing leads to a discontinuous solution in the space of the input parameters and can create additional numerical noise which can disturb the random solution. Alternatives have been proposed in the literature [5][6][7][8][9] to avoid remeshing. In the following, we will focus mainly on uncertainties on the behaviour laws.…”
Section: Stochastic Problemmentioning
confidence: 99%